Cyrano's utopia: where you become what you eat - Staquet, Anne (Cadernos de Literatura Comparada, 2019)
The theme of food might seem futile in view of the questions generally addressed by philosophy. However, in Cyrano de Bergerac's utopian novels, Les États et Empires de la Lune and Les États et Empires du Soleil, the theme of food is strongly linked to the author's philosophy. This is certainly related to Cyrano's materialistic position. To the extent that thought is nothing more than a function of the body, one becomes somehow what one eats. In the same way, death is no longer to be considered as the liberation of a soul, but as a physical transformation process of beings: the putrefaction of a being nourishes plants and worms which will feed birds, which themselves will feed certain mammals. Not only does the distinction between man and animal disappear, but the plants themselves acquire the status of sensitive and reasoned beings.